Palynological characterization of ornamental plants - Helen Sabrine Hoffmann; Denise Monique Dubet da Silva Mouga (Acta Biológica Catarinense, 2023)
Pollen grains are reproductive structures, which have a very resistant coating (exine outer wall and intine inner wall) and exhibit the main morphological components of palynological characterization. Ornamental plants are recognized for their plastic characteristics (flowers, leaves, perfume, fruits) and are generally grown in gardens. Aiming to carry out the palynological characterization of ornamental species, the following species were analyzed: Dietes bicolor (Steud. Klatt ex Sweet, 1866) (Iridaceae), Neomarica candida (Hassl. Sprague, 1928) (Iridaceae), Agapanthus inapertus (Beauverd, 1912) (Amaryllidaceae), Calceolaria tripartita (Ruiz & Pav. 1798) (Calceolariaceae), Erythrina speciosa (Andrews, 1806) (Fabaceae), Begonia radicans (Vell. 1827) (Begoniaceae), Closed buds of the species were collected, which were conserved in acetic acid. The anthers were removed, macerated and acetolyzed. The pollen grains were mounted on microscopy slides, observed under light and scanning electron microscope, photographed and described in terms of unit, size, scope, polarity, symmetry, openings, shape and ornamentation. For the monocotyledons, the grains were in monads, elliptical in amb, heteropolar, large, with bilateral symmetry, monosulcate, with reticulated exine. For the eudicots, the grains were presented in monads, sub-circular/circular amb, isopolar, small/ medium, with radial symmetry, tri-tetracolporate, prolate/prolate-spheroidal shape, with reticulated /striated exine.